2014
DOI: 10.5897/ajmr2014.6859
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Anacardium occidentale L. leaves and barks extracts on pathogenic bacteria

Abstract: The aim of this study was to investigate the antibacterial activity of aqueous, ethanol, ethyl acetate and dichloromethane extracts of two different cashew tree parts (leaf and bark). The susceptibility of strains to the different extracts was evaluated in vitro by disc diffusion method on ten reference strains and nine foods strains. The minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC) were determined respectively by macro-dilution method and seeding on solid medium. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
1
10
0
1
Order By: Relevance
“…The ethyl acetate fraction of A. occidentale leaf did not show antifungal activity against A. flavus and this contradicted the report of Rajesh et al 80 that had ethyl acetate fraction of A. occidentale to inhibit A. flavus. The activity of the ethyl acetate fraction of A. occidentale leaf however supported the report of Chabi et al 81 that the ethyl acetate fraction of A. occidentale leaf showed bacteriostatic and bactericidal effects on nineteen strains of bacteria. The inhibition of B. cereus and P. aeruginosa by A. occidentale leaf extract supported the reports of Mackeen et al 82 It also agreed with Tan and Chan 83 who reported the inhibition of A. occidentale leaf against P. aeruginosa.…”
Section: Antimicrobial Activity Of Anacardium Occidentale Leaf Extractssupporting
confidence: 86%
“…The ethyl acetate fraction of A. occidentale leaf did not show antifungal activity against A. flavus and this contradicted the report of Rajesh et al 80 that had ethyl acetate fraction of A. occidentale to inhibit A. flavus. The activity of the ethyl acetate fraction of A. occidentale leaf however supported the report of Chabi et al 81 that the ethyl acetate fraction of A. occidentale leaf showed bacteriostatic and bactericidal effects on nineteen strains of bacteria. The inhibition of B. cereus and P. aeruginosa by A. occidentale leaf extract supported the reports of Mackeen et al 82 It also agreed with Tan and Chan 83 who reported the inhibition of A. occidentale leaf against P. aeruginosa.…”
Section: Antimicrobial Activity Of Anacardium Occidentale Leaf Extractssupporting
confidence: 86%
“…Leaves and stem barks extracts of A. occidentale were active materials against E. coli, S. aureus, S. epidermidis, P. aeruginosa, P. mirabilis, M. luteus, P. vulgaris, S. oralis, E. faecalis, and C. albicans [19] . Besides that, the stem barks also have potency as an antioxidant [20,21] . To support the potency of the plant tissue extracts, three compounds, which were isolated from methanol extract, were evaluated for their biological activities against some bacteria and DPPH (radical scavenger).…”
Section: Resultsmentioning
confidence: 99%
“…The plant from Brazil has potency as an antiulcer and inhibits the activity of several enzymes like lipooxygenase and cyclooxygenase [20] . In addition, extracts of the leaves and barks of A. occidentale from Benin is active against Escherichia coli, Staphylococcus aureus, S. epidermidis, Pseudomonas aeruginosa, Proteus mirabilis, Micrococcus luteus, P. vulgaris, Streptococcus oralis, Enterococcus faecalis and Candida albicans [21] . The stem barks from Portugal and Nigeria, also has good potential as antioxidants [22,23] and antiinflammatory [24] .…”
Section: Research Papermentioning
confidence: 99%
“…Il est donc nécessaire de favoriser le développement des insecticides naturels à partir des plantes, tel que le baume de cajou encore appelé Cashew Nut Shell Liquid (CNSL). Ce produit issu de la coque de la noix de cajou, possède des propriétés biocides intéressantes sur certains nuisibles (Cavalcante et al, 2003;Chabi et al, 2013;Chabi et al, 2014) ) et en particulier sur les ravageurs de niébé au champ et en stock (Kpoviessi et al 2017). L'usage des plantes pesticides se révèle être une pratique ancestrale en Afrique (Yarou et al, 2017).…”
Section: Introductionunclassified